Status of the Black Dammar Tree (Canarium strictum Roxb.) in Periyar Tiger Reserve, Kerala and the Uses of Black Dammar - Augustine, Jomy; Krishnan, Pramod G. (Indian Forester, 2006)
Periyar Tiger Reserve with more than 62% the tropical evergreen forests is the largest protected area in Kerala state. It is the ideal habitat of the black dammar tree, Canarium strictum Roxb. (Burseraceae). People living in the vicinity of the tiger reserve especially on the Tamil Nadu side heavily subject the population of this tree for the extraction of black dammar. The present status of the black dammar tree including its population structure in the tiger reserve was studied and it was found that the population is in a declining phase with fewer juvenile ones. There are six different kinds of use identified for Black dammar.